Female polyandry affects their sons' reproductive success in the red flour beetle Tribolium castaneum - Bernasconi, Giorgina; Keller, Laurent (My University, 2001)
A potential benefit to females mating with multiple males is the increased probability that their sons will inherit traits enhancing their pre- or post-mating ability to obtain fertilizations. We allowed red flour beetle (Tribolium castaneum) females to mate on three consecutive days either repeatedly to the same male or to three different males. This procedure was carried out in 20 replicate lines, 10 established with wild-type, and 10 with the Chicago black morph, a partially dominant phenotypic marker. The paternity achieved by the sons of females from polyandrous vs. monandrous lines of contrasting morph was assessed in the F1, F2 and F3 generation by mating wild-type stock females to two experimental males and assigning the progeny to either sire based on phenotype. The sons of polyandrous wild-type females achieved significantly higher paternity when mating in the second male role than the sons of monandrous wild-type females. By contrast, when mating in the first male role, males produced by females from polyandrous lines tended to have lower paternity than males from monandrous lines. Both effects were independent of the number of mates of the black competitor's mother, and interacted significantly with the number of progeny laid by the female. These results provide the first evidence that manipulating the number of mates of a female can influence her sons' mating success and suggest a potential trade-off between offence and defence in this species.
Keywords: Coleoptera; mating; polyandry; reproduction; sexual selection; Tenebrionidae; Tribolium castaneum